Genome-Wide Identification and Characterization of Novel Laccase Genes in the White-Rot Fungus Flammulina velutipes - Kim, Hong-Il; Kwon, O-Chul; Kong, Won-Sik; Lee, Chang-Soo; Park, Young-Jin (Mycobiology, 2014)
The aim of this study was to identify and characterize new Flammulina velutipes laccases from its whole-genome sequence. Of the 15 putative laccase genes detected in the F. velutipes genome, four new laccase genes (fvLac-1, fvLac-2, fvLac3, and fvLac-4) were found to contain four complete copper-binding regions (ten histidine residues and one cysteine residue) and four cysteine residues involved in forming disulfide bridges, fvLac-1, fvLac-2, fvLac3, and fvLac-4, encoding proteins consisting of 516, 518, 515, and 533 amino acid residues, respectively. Potential N-glycosylation sites (Asn-Xaa-Ser/Thr) were identified in the cDNA sequence of fvLac-1 (Asn-454), fvLac-2 (Asn-437 and Asn-455), fvLac-3 (Asn-111 and Asn-237), and fvLac4 (Asn-402 and Asn-457). In addition, the first 19~20 amino acid residues of these proteins were predicted to comprise signal peptides. Laccase activity assays and reverse transcription polymerase chain reaction analyses clearly reveal that CuSO4 affects the induction and the transcription level of these laccase genes.